Paisagem e patrimônio: o caso da Vila Industrial em Anápolis – GO - Calaça Júnior, Mário Pinto (2023)
The industry and railroad are part of the history of the city of Anápolis/GO - a city located between Brasília/DF and Goiânia/GO - and have contributed to the economic advancement and the desire for progress of the city’s residents. As it developed, several buildings related to these activities were built, especially in Vila Industrial (a neighborhood where industry and the railroad converge) – such as a mill, industrial warehouses and a railway station. In this sense, the objective is to identify whether in the aforementioned neighborhood there is a built complex that can be part of an industrial heritage collection, understanding its relevance in the urban landscape and what relationship Anapolinos have with it. For this, it was necessary, methodologically, to outline some paths such as: the historical survey, contemplating the trajectory of the railroad and industry in Anápolis, as well as the history of the neighborhood and the consolidation of its urban landscape, through research in archives and city periodicals; the theoretical-conceptual bibliographic review, with contributions to guide the research; finally, the field survey with recognition of the landscape of the neighborhood, together with the application of questionnaires with Anapolinos that contemplates the proposed subjects. In the end, it was possible to understand the place of Anápolis in front of its built set, especially the industrial one – being able to consider it subject to patrimonial recognition.